The Impact of Asymmetric Information on Auto Insurance Policy in Lagos State - Akindipe, Oluwaleke Ebenezer; Tajudeen, Olalekan Yusuf (Acta Universitatis Danubius. Œconomica, 2023)
This study investigates the impact of asymmetric information on auto insurance policies in Lagos State. The main objective is to determine the effect of asymmetric information on affect insurer’s acceptance of risk and claims payment in auto insurance. The scope of the study is the five big insurance companies in Nigeria. The survey research design was used for this study. The study population consists of 15,341, and the sample size is 390. A structured questionnaire was used to gather responses from the respondents, simple percentages and descriptive statistics were used to analyze the study, and a chi-square test was used to test the hypothesis. Based on the findings and analysis of the data, it was clear that it is possible to reduce asymmetric information in the automobile insurance market by ensuring that systems are put in place to get accurate information from the insured and do extensive research about the subject matter. It was concluded that insurance companies in Nigeria recognize the negative impact of asymmetric information on a company’s profitability and investment. It was recommended that targeted stipulations be used frequently to reduce or narrow the chances of asymmetric information auto insurance policies to take the asymmetric information factors into account and alleviate the problem areas.